X/8+3/8=1 x/8-3/8=0 x/8-3/8=1 1-x/8=3/8

X/8+3/8=1 x/8-3/8=0 x/8-3/8=1 1-x/8=3/8
Гость
Ответ(ы) на вопрос:
Гость
х/8 + 3/8 =1 (х+3):8=1 х+3 = 8 х=8-3 х=5 х/8-3/8=0 х-3=0 х=3 х/8-3/8=1 (х-3):8=1 х-3=8 х=8+3 х=11 1-х/8=3/8 1=х/8+3/8 1=(х+3):8 8=х+3 х=8-3 х=5
Гость
х/8 + 3/8 = 1                    х/8 - 3/8 = 0 х/8 = 1 - 3/8                     х/8 = 3/8 х/8 = 5/8                          х = 3/8 * 8 х = 5/8 * 8                        х = 3 х = 5 х/8 - 3/8 = 1                     1 - х/8 = 3/8 х/8 = 1 + 3/8 = 1 3/8         х/8 = 1 - 3/8 х/8 = 11/8                        х/8 = 5/8  х = 11/8 * 8                      х = 5/8 * 8 х = 11                              х = 5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы